Perilaku Profesional Tenaga Medis terhadap Tanggung Jawab Etik dan Transaksi Terapeutik dalam Menjalankan Kewenangan Klinis - Vini H. R. Gosal; Aaltje E. Manampiring; Caecilia Waha (Universitas Sam Ratulangi, 2022)
Abstract: Professional medical personnel must have elements of professionalism, basic principles of medicine and professional ethics in carrying out their profession. Clinical privilege is a doctor's special right obtained through the credential process by the Medical Committee. This study aimed to analyze the medical personnel towards ehical responsibility and therapeutic transactions in doing their clinical privilege. This was a qualitative study using case study method. Subjects were eight people consisting of general practitioners, specialists, the chairman of the Medical Committee, and the sub-committee for credentials of Rumah Sakit Umum Manado Medical Center. Primary data were obtained through in-depth interviews and observation guidelines. Validity of the data was done using the triangulation method. The results showed that the behavior of doctors was in accordance with the element of professionalism, but not all of them applied the professional behavior ethics according to hospital standard operating procedure (SOP). Based on the implementation of therapeutic transactions, not all of them have carried out the doctor's obligation to explain the patient's diagnosis completely and in detail simplly to be understood. The results of implementation of the credential were suitable to the procedure, but for evaluation, it was not optimal due to the re-credential was not carried out. In conclusion, not all medical personnel applied the professional behavior ethics according to hospital (SOP). Monitoring and evaluation through re-credentialing of medical personnel had not been performed at Manado Medical Center.Keywords: professional behavior; ethics; therapeutic transactions; clinical privilegeÂ Abstrak: Tenaga medis yang profesional harus memiliki unsur-unsur profesionalisme, prinsip dasar kedokteran dan etika profesi dalam menjalankan profesinya. Kewenangan klinis merupakan hak khusus dokter yang didapatkan melalui proses kredensial oleh Komite Medik. Penelitian ini bertujuan untuk menganalisis perilaku profesional tenaga medis terhadap tanggung jawab etik dan transaksi terapeutik dalam menjalankan kewenangan klinis. Jenis penelitian ialah kualitatif dengan metode studi kasus. Subjek penelitian berjumlah delapan orang terdiri dari dokter umum, dokter spesialis, ketua Komite Medik dan sub komite kredensial Rumah Sakit Umum Manado Medical Center. Data penelitian diperoleh melalui wawancara mendalam dan pedoman observasi. Validitas data menggunakan metode triangulasi. Hasil penelitian menunjukkan perilaku dokter sesuai dengan unsur profesionalisme, tetapi belum semua menerapkan etika perilaku profesional sesuai standar prosedur operasional (SPO) Rumah Sakit. Dalam pelaksanaan transaksi terapeutik, belum semua dokter melaksanakan kewajibannya yaitu menjelaskan diagnosa pasien secara lengkap dan rinci dengan bahasa yang mudah dipahami. Pelaksanaan kredensial sesuai dengan prosedur, tetapi untuk evaluasi belum optimal karena pelaksanaan re-kredensial tidak dilakukan. Simpulan penelitian ini ialah belum semua dokter menunjukkan sikap dan perilaku sesuai SPO Rumah Sakit dan belum dilakukan monitoring dan evaluasi kembali melalui proses re-kredensial dokter umum dan dokter spesialis di Manado Medical Center.Kata kunci: perilaku professional; etik; transaksi terapeutik; kewenangan klinis